CD9 in acute myeloid leukemia: Prognostic role and usefulness to target leukemic stem cells - Lucas Touzet; Florent Dumezy; Christophe Roumier; Céline Berthon; Claire Bories; Bruno Quesnel; Claude Preudhomme; Thomas Boyer (Cancer Medicine)
Abstract CD9 is a cell surface protein and belongs to the tetraspanin family. Its role in carcinomagenesis has been widely studied in solid tumors but remains controversial, depending on the cancer type. Although CD9 seems to be associated with unfavorable outcome and disease progression in acute lymphoblastic leukemia (ALL), this marker has not yet been studied in acute myeloid leukemia (AML). First, we explored its prognostic role and its association with biological factors in a cohort of 112 AML patients treated with intensive chemotherapy. CD9 was expressed in 40% of AML and was associated with a favorable outcome (event‐free survival and relapse‐free survival) in univariate (P = 0.009 and P = 0.048, respectively) and multivariate (P = 0.004 and P = 0.039, respectively) analyses. Interestingly, CD9 expression was different between the more immature physiologic and AML cells (CD34+CD38−) as it was also expressed in AML on putative leukemic stem cells (LSCs) but not on hematopoietic stem cells (HSCs). Hence, CD9 could be a very relevant marker for minimal residual disease (MRD) monitoring in AML based on LSC targeting.